2015
DOI: 10.1371/journal.pone.0135799
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Microarray Data of Rainbow Trout Fry Gonad Differentiation Modulated by Ethynylestradiol

Abstract: Sex differentiation in fish is a highly labile process easily reversed by the use of exogenous hormonal treatment and has led to environmental concerns since low doses of estrogenic molecules can adversely impact fish reproduction. The goal of this study was to identify pathways altered by treatment with ethynylestradiol (EE2) in developing fish and to find new target genes to be tested further for their possible role in male-to-female sex transdifferentiation. To this end, we have successfully adapted a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In medaka some cyst germ cells were germline stem cells with bipotential activity that differentiate in to oogonia but in the absence of E2 are capable to differentiate into spermatogonia [Paul-Prasanth et al, 2013]. The mode of action of feminizing EE2 (ethinylestradiol) treatment was studied in rainbow trout fry/juveniles with a meta-analysis of microarray data showing a rapid and strong decrease of key testis genes, notably those involved in androgen synthesis [Depiereux et al, 2015]. It highlighted new pathways such as the progesterone-oocyte maturation pathway with several genes of the germline, cell division and oocyte meiosis represented and the peroxisome proliferator-activated receptor (PPAR) signaling pathway containing genes from the nuclear hormone (steroid/thyroid/retinoid) receptor family that perhaps regulate aromatase levels.…”
Section: Revisiting Old Players Of Sex Differentiationmentioning
confidence: 99%
“…In medaka some cyst germ cells were germline stem cells with bipotential activity that differentiate in to oogonia but in the absence of E2 are capable to differentiate into spermatogonia [Paul-Prasanth et al, 2013]. The mode of action of feminizing EE2 (ethinylestradiol) treatment was studied in rainbow trout fry/juveniles with a meta-analysis of microarray data showing a rapid and strong decrease of key testis genes, notably those involved in androgen synthesis [Depiereux et al, 2015]. It highlighted new pathways such as the progesterone-oocyte maturation pathway with several genes of the germline, cell division and oocyte meiosis represented and the peroxisome proliferator-activated receptor (PPAR) signaling pathway containing genes from the nuclear hormone (steroid/thyroid/retinoid) receptor family that perhaps regulate aromatase levels.…”
Section: Revisiting Old Players Of Sex Differentiationmentioning
confidence: 99%
“…As an analog of E2, EE2 provides a clear example of how a XE can alter reproductive processes. An in vivo study in the fry of rainbow trout revealed that exposure up to 10 μg/L EE2 enriched pathways related to the cell cycle and DNA replication, and demonstrated the ability of EE2 to disrupt gonad differentiation [ 100 ]. While sex differentiation in fish is more labile than in mammals, the ability of EE2 to alter transcriptional patterns during female gonad differentiation in male fish demonstrates the estrogenic effects of EE2 [ 100 ].…”
Section: Environmental and Human Health Implications Of Edc Exposurementioning
confidence: 99%
“…To identify the potential sex-related miRNAs, we analyzed the DE-miRNAs targeting sex-associated genes, functions, or pathways, including progesterone-mediated oocyte maturation, the TGF-beta signaling pathway, and the Wnt signaling pathway, which are known to be involved in sex determination and differentiation in other fish species (Herpin et al, 2013;Depiereux et al, 2015;Jia et al, 2018). After establishing a DE-miRNA-mRNA-sex-related pathway network, we found that 22 DE-miRNAs potentially regulated the sex-related pathways by targeting 18 mRNAs (Figure 5A).…”
Section: Analysis Of Sex-related De-mirnasmentioning
confidence: 99%